Analysis on Willingness to Pay at the Ecotourism Destination, Cigamea Waterfall, Halimun-Salak National Reserve - MUNANDAR, Aris; GUNAWAN, Andi; NURAZIZAH, Ghoitsa Rohmah; KUSUMOARTO, Andrianto (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
Cigamea Waterfall is one of the ecotourism destinations situated in area of Salak Resort II of Halimun-Salak National Reserve (HSNR) Indonesia that can be partialy developed. The area consists of sub montanes forest and montane forest categorized as humid tropical forest. The uniqueness and the beauty of the flora, fauna, natural phenomena, and the natural condition become attraction for people to visit the area and willingness to pay for contribution fee. This fee is used as management funding to preserve the area. A demand for a commodity is trigered by willingness affordibility in buying that commodity (willingness to pay). The research analyzed willingness to pay by visitors to enjoy the beauty of Cigamea Waterfall. Logit method with descriptive quantitative approach was used in this study. Several stages in this study included: (1) analysing visitors’ trend; (2) analysing respondents’logit regression towards willingness to pay (WTP); (3) analysing willingness to pay. During this research, this ecosystem may be the last home for Leopard which stated vulnerable (VU) by REDLIST of IUCN and may be the last home for other endangered (EN) species. Based on the analysis on the responses of 342 respondents concerning their willingness to pay for contribution, 202 of the (59,1%) were willing to pay while the rest 140 respondents (48,9%) refused to pay. The average value of willingness to pay obtained was 15.000 IDR (1 USD = 14.000 IDR per year 2016) paid to enjoy the beauty of Salak Resort II, HSNR. This value was higher than that of the ticket per ecotourism object charged by the management of the resort averaging 7.500 IDR. Based on respondents’ willingness to pay, the average of the willingness to pay to enjoy the Cigamea waterfall ecotourism object was 14.000 IDR. The Willingness to pay to get into Cigamea Waterfall was lower than that for entering Salak Resort II, HSNR. Visitors willingness to visit Cigamea Waterfall ecoturism object due to the existence of forest and some natural phenomena, river as ecological corridors of the area, easy access through trekking path corridors in the forest margin (edges) as well as the potential of the flora and the fauna. The potential value of Cigamea Waterfall was 3,66 (out of 1 to 7 scale of Guideline of Ministry of Forestry), that of the flora was 2,48, while value of the fauna was 3,29.  This also support claims toward a new paradigm of value that ecosystem is not only treated as supply depot of resources but also treated as oikos (home for us and other living organism).